Tradução e validação da exercise benefits/barriers scale aplicação em idosos - Victor, Janaína Fonseca (2007)
With this research one aimed at making a transcultural adaptation of the Exercise Benefits/Barriers Scale (EBBS) for Portuguese language and at verifying the psychometric properties of the EBBS to detect the perception about benefits and barriers of practicing physical activities by aged people. The EBBS was exposed to the process of transcultural adaptation proposed by the Guidelines for the cross-cultural adaptation process. The reliability of the EBBS was verified by the alpha of Cronbach and by the test-retest through the w coefficient of Kendall. The validity was analyzed by the content validity (opinion of five specialists) and construct validity (association between the results of EBBS and the sociodemographic, clinical and lifestyle variables). It was a methodological research with quantitative approach, conducted in a Family Health basic unit (UBASF) in Fortaleza-CE. The sample was composed of 214 aged people attended by the professionals of the Family Health Program (PSF). The data collection was held from September through December, 2005, using as instruments the translated version of the EBBS and a form for the characterization of the aged people. The results reveal that, in the transcultural adaptation, one item of the scale was taken away because it showed ambiguousness and, out of the 42 items that compose the EBBS, 12 had to be exemplified to be understood by the population. The alpha of Cronbach of the total scale was of (0.94) and the test-retest (0.60). The content validity showed that new items have to be inserted. The construct validity showed that there was association statistically significant between the EBBS and the variables: school years (p= 0.0001), with whom he/she lives (p= 0.03), lifestyle (p= 0.0001), physical activity practice (p= 0.0001) and that these results are coherent with the literature. The application of the EBBS showed that the aged people from this study notice more benefits than barriers for physical activity; the benefits less noticed were referent to the prevention of diseases, and the barriers identified were related to the time to do the physical activity, to the physical effort and to the lack of family encouragement. After the conduction of this study, one obtained a reliable instrument able to evaluate the perception of benefits and barriers for the practice of physical activity by aged people. This can be used largely by nurses and other health professionals, contributing, thus, for future studies with the themes health promotion and physical activity. One still suggests the application of the translated and adapted version of the EBBS in different populations, in order to verify the reliability and the validity of the instrument, because with the adhesion of new researchers one will be able to reach a stable and reapplicable scale.